1995
DOI: 10.1016/0014-5793(94)01453-8
|View full text |Cite
|
Sign up to set email alerts
|

An SH3 domain is required for the mitogenic activity of microinjected phospholipase C‐γ1

Abstract: Phospholipase activity is elevated in dividing cells. In response to growth factor stimulation, phospholipase C-y (PLC-3') binds to activated tyrosine kinase receptors via SH2 binding domains, resulting in phosphorylation of PLC-y and activation of its enzyme activity. These observations suggest that PLC-y participates in the signal transduction pathway employed by growth factors to promote mitogenesis. Consistent with this hypothesis, microinjection of purified bovine PLC-y into quiescent fibroblasts has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 37 publications
(39 reference statements)
1
47
2
1
Order By: Relevance
“…The previous observation that overexpression of a catalytically inactive PLC-␥1 initiated a mitogenic response suggested that PLC-␥1 possesses an activity independent of its lipase activity (36). Moreover, the observation that microinjection of a recombinant protein containing the SH region of PLC-␥1 was sufficient to induce a mitogenic response (37,38) suggests that this additional activity is mediated by the SH region, which likely interacts with other mitogenic signaling intermediates. The C-SH2 domain of PLC-␥1 thus might be required for this linker function associated with the mitogenic activity of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The previous observation that overexpression of a catalytically inactive PLC-␥1 initiated a mitogenic response suggested that PLC-␥1 possesses an activity independent of its lipase activity (36). Moreover, the observation that microinjection of a recombinant protein containing the SH region of PLC-␥1 was sufficient to induce a mitogenic response (37,38) suggests that this additional activity is mediated by the SH region, which likely interacts with other mitogenic signaling intermediates. The C-SH2 domain of PLC-␥1 thus might be required for this linker function associated with the mitogenic activity of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-injection of purified PLC-γ1 into quiescent NIH 3T3 cells induced DNA synthesis and the injection of antibodies against PLC-γ1 into the same cells blocked the serum induced DNA synthesis (Smith et al, 1989;Smith et al, 1990). Recent studies have shown that a PLC-γ1 mutant lacking the lipase activity still induced DNA synthesis, implying that regions other than the catalytic domain may be responsible for the mitogenic effect (Smith et al, 1994;Huang et al, 1995). Among multiple PLC-isozymes, only PLC-γ isozyme contains the Src-homology domains (SH domain) (two SH2 domains and one SH3 domain) that are also found in a number of proteins involved in the regulation of cell proliferation and differentiation (Pawson and Nash, 2000).…”
Section: Plc-γ γ γ γ1 In Cellular Proliferationmentioning
confidence: 99%
“…The SH3 domain of PLC-γ1 is known to be responsible for the mitogenic effect of PLC-γ1. Namely, micro-injection of the GST-fused SH3 domain of PLC-γ1 into G0 growth arrested NIH 3T3 cells induced DNA synthesis (Huang et al, 1995;Smith et al, 1996). This mitogenic activity of PLC-γ1 or possible effector protein that could bind to the SH3 domain of PLC-γ1 has been the intense subject for study in many laboratories.…”
mentioning
confidence: 99%
“…In addition to the lipase activity of PLC-g, protein ± protein interactions through the SH domain are also involved in the PLC-g-mediated signaling pathway. When a truncated PLC-g1 containing the SH2-SH2-SH3 domains (Smith et al, 1996), or a lipase inactive mutant of PLC-g1 are microinjected into NIH3T3 cells, they induce DNA synthesis (Huang et al, 1995), which indicates that the SH domain of PLC-g1 is involved in PLC-g1-mediated signaling. It was also reported that the SH3 domain of PLC-g1 interact with SOS-1, and is involved in SOS1-mediated p21 Ras activation (Kim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%